CORAK PENAFSIRAN MUHAMMAD ABDUH DAN MUHAMMAD RASYID RIDHA DALAM TAFSIR AL-MANAR - Mohammad Fattah; Ahmad Mahfud; Fitrah Sugiarto; Syaifatul Jannah (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
Tafsir Al-Manar is an interpretation that marks the world of modern interpretation, which was written by Muhammad Rasyid Ridha from the teachings of his teacher, Muhammad Abduh. The interpretation is of the Tafsir bi al-Rayi type with the Tahlili interpretation method and the pattern Al-Adabi wa al-Ijtimai. The novelty of this interpretation lies in its style, which focuses on social issues. Therefore, every style of Al-Adabi wa al-Ijtimai must be different according to the time, place and social problems it faces. The problem discussed in this study is how the idea of the pattern of Al-Adabi wa al-Ijtimai and the social issues contained therein. This research paradigm uses a descriptive qualitative approach with descriptive and deductive methods. The data source used is the interpretation of Al-Manar by Muhammad Abduh and Muhammad Rasyid Ridha, by analyzing the biographies of both of them as well as the social issues alluded to in the interpretation of Al-Manar. The results found, that the idea was motivated by the decline of Muslims and influenced by the empiricism of Muhammad Abduh and Muhammad Rasyid Ridha. Meanwhile, from the social issues contained in Al-Manar's interpretation, all of them refer to the optimization of reason as a source of knowledge.